IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM PEMBELAJARAN IPAS PADA PESERTA DIDIK KELAS V DI SD NEGERI 1 CEMPAGA BANGLI - Ni Kadek Puspitayanti; I Made Wiguna Yasa; I Gede Tilem Pastika (JPDI (Jurnal Pendidikan Dasar Indonesia), 2026)
The use of the learning model is based on a teaching that involves the conscious action of controlling the learning process of students. The learning process of students is a fundamental action in all forms of education where learning not only involves results but also the process of acquiring knowledge and the quality of learning outcomes is determined by the quality of the process with the interaction in the learning process.This study discusses the following problems: (1) The form of implementation of the jigsaw-type cooperative learning model in social studies learning in grade V students at SD Negeri 1 Cempaga Bangli, (2) Obstacles and efforts made in its implementation, (3) Implications of the implementation of the jigsaw-type cooperative learning model in learning. This qualitative descriptive research aims to find out the form of implementation, obstacles, efforts and implications of the implementation of the jigsaw-type cooperative learning model in science learning in grade V students at SD Negeri 1 Cempaga Bangli. This research was analyzed using constructivism theory, behaviorism theory, and motivation theory. The data collection method uses observation, interview, documentation studies, and literature studies. Based on the results of the study, it shows that (1) The form of implementation of the jigsaw-type cooperative learning model in social studies learning refers to several stages that are carried out, namely the planning stage, the implementation stage and the evaluation stage. (2) The obstacles faced include difficulties in guiding students with different abilities, difficulties in monitoring group members evenly, limited time, lack of courage of students in communicating and limited classrooms for group discussion activities. Efforts to overcome these obstacles include arranging the division of assignments in groups, providing written discussion guides, managing time and utilizing infrastructure, and organizing classrooms. (3) The implementation of the jigsaw-type cooperative learning model has positive implications for students' learning attitudes and learning outcomes.